Carry trade and currency crash risk - Merve Kutuk; Sweder van Wijnbergen (Tinbergen Institute, 2025)
This paper examines the role of currency crash risk in explaining the persistent profitability of carry trades. Focusing on the US Dollar-Turkish Lira market, we construct three forwardlooking measures of crash risk: risk reversals, crash probabilities from option-implied distributions, and jump risk from a jump-diffusion model. Using survey-based exchange rate expectations, we separate ex ante carry premia from ex post surprises. Our results show that higher crash risk significantly increases expected returns, indicating that investors demand compensation for bearing such risk rather than arbitraging away mispricing. Shapley decomposition attributes over 20% of the explained variance in expected carry returns to crash risk, while balance sheet constraints and global risk aversion further reinforce premia. A comparison of hedged and unhedged strategies reveals that 46-77% of carry returns reflect compensation for crash exposure.
Keywords: F13; G01; G10; G12; G15; 330; Exchange rates; currency crash risk; mispricing; dollar exchange rate; bank currency mismatches